Synthesis and Electroanalytical Performance of a Composite Material Based on Poly(3,4-ethylenedioxythiophene) Doped with Lignosulfonate - Grzegorz Milczarek; Tomasz Rebis (International Journal of Electrochemistry)
3,4-ethylenedioxythiophene (EDOT) was electropolymerized in the presence of sodium lignosulfonate (LS) at constant current density of 0.25 mA cm−2. As a result, a thin composite film consisting of poly(3,4-Ethylenedioxythiophene) and LS (PEDOT/LS) was deposited on the electrode surface. Unlike PEDOT, PEDOT/LS shows appreciable redox activity due to LS-derived quinone moieties with diffusion-like charge propagation across the film thickness. The film-modified gold electrodes can be used as voltammetric sensor of uric acid (UA) in the presence of ascorbic acid (AA). Interestingly, the UA response is catalysed by the presence of AA, and for high AA/UA concentration ratios more than 10-fold enhancement of the UA peak currents are apparent.